Toxoplasma gondii infection in wild boars (Sus scrofa) from the State of São Paulo, Brazil: Serology, molecular characterization, and hunter's perception on toxoplasmosis - Machado, Dália Monique Ribeiro [UNESP]; de Barros, Luiz Daniel; de Souza Lima Nino, Beatriz; de Souza Pollo, Andressa [UNESP]; dos Santos Silva, Ana Clécia; Perles, Lívia [UNESP]; André, Marcos Rogério [UNESP]; Zacarias Machado, Rosângela [UNESP]; Garcia, João Luis; Lux Hoppe, Estevam Guilherme [UNESP] (Elsevier, 2021)
The consumption of wild boar meat, common in many countries, became popular in Brazil after the hunting of these animals was authorized in 2013. The meat of these animals is often consumed by hunters and their social groups, and their offal is occasionally used as supplemental food in the diet of hunting dogs. Given the high frequency of foodborne diseases related to wild boar meat consumption in other countries, including toxoplasmosis, knowledge on these diseases is essential for risk assessment and elaboration of education campaigns for the exposed public. Thus, this study aimed diagnosing, isolating, and genotyping Toxoplasma gondii in hunted wild boars. For that, we obtained samples of serum and tissues (brain, tongue, diaphragm, and heart) from 26 wild boar hunted in three areas in São Paulo State, Brazil, based on convenience sampling strategy. The serum samples were submitted to the indirect immunofluorescence reaction test (IFAT) test while the tissue samples (n = 22) were used to perform a bioassay in mice to isolate the parasite. The isolated samples were genetically characterized by PCR-RFLP with SAG1, 5′ and 3’ SAG2, alt.SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, and Apico markers. Questionnaires were also formulated and applied to wildlife hunters to assess knowledge about toxoplasmosis. The seroprevalence of T. gondii was 76.9% (20/26), with titers ranging from 16 to 1024. Viable parasites accounted for 4.5% (1/22) of the samples. The ToxoDB #6 genotype of TgJava1 alone was detected. Most interviewed hunters, 84.2% (16/19) consume game meat and a few of them (15.7%; 3/19) prefer undercooked meat. Also, 15.7% (3/19) of the hunters reported supplementing their hunting dogs' diet with wild boar meat and/or offal. As antibodies to T. gondii were detected in 76.9% (20/26) of the studied wild boars, we concluded that infection by T. gondii is frequent in wild boars used for human and animal consumption in the studied areas. Although genotype #6 is commonly found in Brazil in domestic animals, wild animals, and humans, causing everything from mild clinical symptoms to death, this study found, for the first time, the detection of this genotype in wild boars. These results also reaffirm the importance of these animals as a possible source of T. gondii infection for humans and domestic animals.
Keywords: Game meat; Genotyping; Invasive species; Toxoplasmosis; Zoonosis